1978
DOI: 10.3758/bf03336761
|View full text |Cite
|
Sign up to set email alerts
|

Eating and drinking in rats with anterior or posterior amygdaloid lesions

Abstract: Electrolytic lesions were placed bilaterally either in the anterior or in the posterior amygdala of albino rats. In terms of comparisons of lesion data with data for animals with corresponding control operations, anterior amygdaloid lesions had no significant influence on either water or overall food intake nor on body weight, while posterior amygdaloid lesions significantly increased water consumption without reliably altering food intake or body weight. It is proposed that the dorsal portion of the anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Numerous studies have examined the effects of amygdaloid lesions on food intake and body weight in rats, resulting in a similar collection of inconsistent and contradictory results. Initial studies that employed large lesions that destroyed most of the amygdala reported hypophagia and weight loss (4,12,41,56,61,64,65). Subsequent studies of rats with smaller lesions aimed at the basolateral and/or lateral nuclei reported weight gain (8,23,43), no change in body weight (18,28,40,45,58,60), or even weight loss (14).…”
mentioning
confidence: 99%
“…Numerous studies have examined the effects of amygdaloid lesions on food intake and body weight in rats, resulting in a similar collection of inconsistent and contradictory results. Initial studies that employed large lesions that destroyed most of the amygdala reported hypophagia and weight loss (4,12,41,56,61,64,65). Subsequent studies of rats with smaller lesions aimed at the basolateral and/or lateral nuclei reported weight gain (8,23,43), no change in body weight (18,28,40,45,58,60), or even weight loss (14).…”
mentioning
confidence: 99%
“…The result was hypophagia and weight loss (e.g., Refs. 5,26,111,179,197,207,208). Subsequent studies that used smaller lesions to target specific amygdaloid nuclei reported inconsistent and conflicting results regarding daily food intake and body weight.…”
Section: Lesion Studies With Ratsmentioning
confidence: 99%